Changes in nutrition-related practices among college students after completing a general education course on nutrition - Juanico, Clarissa B.; Bernardo, Aiza Kris M. (2018)
Nutrition plays a preventive role in obesity and obesity-related diseases across an individual’s life span. Due to the proliferation of high-caloric foods, the risk of becoming overweight has increased among adolescents. Nutrition education, combined with proper food choices and meal selection, may offer a promising approach to achieve optimum nutrition and combat overweight and obesity among Filipino adolescents. A total of 118 college students enrolled in a general education course on nutrition, NASC 6 (Food and Nutrition for a Healthy Life), during the 1st semester, AY 2015-2016, participated in this study. Survey questions on practices related to food and nutrition were administered through a PowerPoint presentation. A set of meals that used menu labels was also shown to respondents to gather information on factors affecting meal selection. Baseline and endline data were collected at the start and end of the semester, respectively. Results indicated that the number of participants who never skipped breakfast doubled, while those who read food labels increased by 18%. Findings also showed that participants select meals based on palatability, prices, and nutritional/caloric value, both before and after attending the nutrition course. Meanwhile, participants exhibited increased knowledge on good nutrition-related practices after completing the nutrition-related course. Moreover, menu labeling stimulated young individuals to consider the nutritional value of meals during food selection, both before and after attending the course.
Keywords: Food preferences